Protection Law to Power Work Personal Branding in Social Media (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
Personal branding is a factor that already exists in every individual, with the personal branding that is formed in each community or individual being different depending on the surrounding environment. Where personal branding correlates with the communication carried out as well as from that process later utilized in the world Work. Organization The company has divisions that have been divided to facilitate performance within the company and make it more effective. This will form the trust and respect shown to managers by employees. When someone wants to build their personal brand, they must pay attention to aspects of skill set, aura and identity. These three aspects are very important in building and developing personality branding individual, so that the result maximum. No only just do Personal branding by sharing photos or various actual activities is felt to have less than optimal impact, and can even be contradictory to the original goal.